Transition-Metal-Free Synthesis of Pyrrolo[1,2-a]pyrazines via Intramolecular Cyclization of N-Propargyl(pyrrolyl)enaminones - Sobenina, Lyubov N.; Sagitova, Elena F.; Ushakov, Igor A.; Trofimov, Boris A. (Synthesis, 2017)
A concise transition-metal-free strategy for the synthesis of pyrrolo[1,2-a]pyrazines with enone substituents has been developed. It includes the following key steps: (a) cross-coupling of pyrroles with acyl(bromo)acetylenes in solid alumina at room temperature to give 2-(acylethynyl)pyrroles; (b) addition of propargylamine to the above acetylenes to form the corresponding N-propargylenaminones; and (c) chemo- and stereoselective base-catalyzed (Cs2CO3/DMSO) intramolecular cyclization of the synthesized propargylic derivatives to form (acylmethylidene)pyrrolo[1,2-a]pyrazines of Z-configuration.
Keywords: pyrroles; acylacetylenes; enaminones; intramolecular cyclization; pyrrolo[1,2-a]pyrazines